Explorations in Reported Moral Behaviors, Values, and Moral Emotions in Four Countries - Myyry, Liisa; Helkama, Klaus; Silfver-Kuhalampi, Mia; Petkova, Kristina; Valentim, Joaquim Pires; Liik, Kadi (Frontiers in Psychology, 2021)
University students (n=758) from Bulgaria, Estonia, Finland, and Portugal were given a list of 30 morally relevant behaviours (MRB), the Schwartz Value Survey (PVQ40) and Tangney’s TOSCA, measuring empathetic guilt, guilt over norm-breaking, and shame. A factor analysis of MRB yielded 4 dimensions: prosocial behaviours, interpersonal transgressions, antisocial behaviours and secret transgressions. Prosocial behaviours were predicted by self-transcendence – self-enhancement (SET) value contrast only while the three transgression categories were associated with both SET and openness to change – conservation (hedonism – conformity) contrast. Norm-breaking guilt was more strongly associated with behaviours than were empathetic guilt and shame. However, shame was (positively) associated with secret transgressions in three countries, after values were taken into account. The associations were strongest in Bulgaria and Estonia while fewer associations were found in Finland and Portugal. The implications of the findings for the cross-cultural psychology of morality are discussed.